2021
DOI: 10.3390/ma14040753
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Structural, and Dielectric Properties of Composites Based on Thermoplastic Polymers of the Polyolefin and Polyurethane Type and BaTiO3 Nanoparticles

Abstract: In this work, new films containing composite materials based on blends of thermoplastic polymers of the polyurethane (TPU) and polyolefin (TPO) type, in the absence and presence of BaTiO3 nanoparticles (NPs) with the size smaller 100 nm, were prepared. The vibrational properties of the free films depending on the weight ratio of the two thermoplastic polymers were studied. Our results demonstrate that these films are optically active, with strong, broad, and adjustable photoluminescence by varying the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
(67 reference statements)
4
15
0
Order By: Relevance
“…After our best knowledge, to date, no study has been reported on composites based on TPU:TPO blends and CNs of the type BaSrTiO 3 or SrTiO 3 . In comparison with the our previous study reported on the composites based on the TPU:TPO blends and the BaTiO 3 particles [ 12 ], in this work, new information will be reported about the following: (i) the adsorption of thermoplastic polymers onto the surface of CNs of the type BaSrTiO 3 and SrTiO 3 , (ii) the role of CNs, BaSrTiO 3, and SrTiO 3, onto the photoluminescence process of the TPU:TPO blend, and (iii) the dielectric and conductive proprieties of the composites based on the TPU:TPO and CNs as well as their mechanisms that take place. In order to highlight this progress, herein, we report structural, optical, dielectric, and conductive properties of the TPU:TPO/CNs composites using X-ray diffraction (XRD), Raman scattering, Fourier-transform infrared (FTIR) absorption, photoluminescence, and dielectric spectroscopy as investigation methods.…”
Section: Introductionmentioning
confidence: 47%
See 3 more Smart Citations
“…After our best knowledge, to date, no study has been reported on composites based on TPU:TPO blends and CNs of the type BaSrTiO 3 or SrTiO 3 . In comparison with the our previous study reported on the composites based on the TPU:TPO blends and the BaTiO 3 particles [ 12 ], in this work, new information will be reported about the following: (i) the adsorption of thermoplastic polymers onto the surface of CNs of the type BaSrTiO 3 and SrTiO 3 , (ii) the role of CNs, BaSrTiO 3, and SrTiO 3, onto the photoluminescence process of the TPU:TPO blend, and (iii) the dielectric and conductive proprieties of the composites based on the TPU:TPO and CNs as well as their mechanisms that take place. In order to highlight this progress, herein, we report structural, optical, dielectric, and conductive properties of the TPU:TPO/CNs composites using X-ray diffraction (XRD), Raman scattering, Fourier-transform infrared (FTIR) absorption, photoluminescence, and dielectric spectroscopy as investigation methods.…”
Section: Introductionmentioning
confidence: 47%
“…The preparation of the composite membranes based on the TPU:TPO 2:1 blend and CNs was performed according to ref. [ 12 ]. Briefly, the TPU:TPO 2:1/CNs membranes were prepared as follows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the sensitive and informative methods for studying such complex low-dimensional systems is impedance spectroscopy in a wide frequency range [ 38 , 39 , 40 , 41 , 42 , 43 ]. Especially important for the study of electronic processes, possible migration of ions, etc., is impedance spectroscopy at low frequencies in the presence of a constant component of the electric field.…”
Section: Introductionmentioning
confidence: 99%